Konsep Persatuan Dengan Kematian Dan Kebangkitan Kristus Berdasarkan Roma 6:1-14 - Hanny Frederik (Jurnal Jaffray, 2015)
Persatuan orang percaya dengan Kristus adalah doktrin yang merupakan pemikiran kunci dalam ajaran Tuhan bahkan sangat penting bagi teologi Paulus sehingga seorang penafsir, James S. Stewart menyebutnya sebagai “inti dari agama Paulus.” Menurut hasil uraian tentang konsep persatuan dengan kematian dan kebangkitan Kristus berdasarkan Roma 6:1-14, maka penulis menarik beberapa kesimpulan sebagai berikut: Pertama, orang percaya telah dipersatukan dengan kematian dan kebangkitan Kristus melalui baptisan, yang berarti ia turut serta mengalami peristiwa-peristiwa yang dialami oleh Kristus dalam sejarah, yakni penyaliban, kematian, penguburan dan kebangkitan Kristus. Kedua, persatuan dengan kematian dan kebangkitan Kristus mengakibatkan berlalunya ciptaan lama, yaitu kematian manusia lama sebagai status atau kedudukan seseorang dalam persekutuannya dengan Adam. Kematian Kristus adalah kematian bagi dosa, karena itu dalam persatuan dengan kematian Kristus, orang percaya juga telah mati bagi dosa. Ketiga, persatuan dengan kematian dan kebangkitan Kristus menghasilkan ciptaan baru, yaitu kehidupan baru sebagai status atau kedudukan orang percaya dalam persekutuan dengan Kristus. Keempat, kehidupan yang berpadanan dengan status baru orang percaya dalam Kristus adalah kehidupan dalam pengudusan yang meliputi hidup dalam pertobatan dan hidup untuk melayani Allah.The unity of the believer with Christ is a doctrine which is a key thought in the teaching of Jesus, moreover it is very important for Paul’s theology such that one commentator, James S. Stewart, delineates it as the “Man in Christ: The Vital Elements of St. Paul’s Religion.” Based upon the results of an analysis about the concept of unity in the death and resurrection of Christ based upon Romans 6: 1-14, the author draws several conclusions as follows: First, believers have been made one with the death and resurrection of Christ through baptism, which means the believer participates in the events which were historically experienced by Christ, that is, the crucifixion, death, burial, and resurrection of Christ. Second, unity with the death and resurrection of Christ causes the passing of the old creation; the death of the old man as the status or position of a person regarding their relationship to Adam. The death of Christ is a death to sin, because in the unity with the death of Christ, a believer has also died to sin.  Third, unity with the death and resurrection of Christ produces a new creation, that is, a new life, with the status or position of a believer regarding their relationship to Christ. Fourth, a life which is in harmony with the new status of a believer in Christ is a life in the process of sanctification, which encompasses living in repentance and living to serve God.